2007
DOI: 10.2169/internalmedicine.46.0015
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Associated Systemic Lupus Erythematosus in an Elderly Man

Abstract: The predominantly young woman-orientated systemic lupus erythematosus (SLE) is a disease that involves an extremely complicated and multifactorial interaction of various genetic and environmental factors. Crystalline silica (Si) may act as an immunoadjuvant to increase secretions of inflammatory endogenous substances and antibody production. In addition, previous studies have suggested that exposure to Si may induce SLE. Although the biologic mechanism of Si in SLE is unclear, defective apoptosis leading to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 24 publications
(7 reference statements)
0
20
0
1
Order By: Relevance
“…The typical autoimmune disorders complicated with silicosis include rheumatoid arthritis (well known as Caplan syndrome) [5,6], systemic lupus erythematosus (SLE) [7,8], systemic sclerosis (SSc) [9,10], and anti-neutrophil cytoplasmic antibody (ANCA)-related vasculitis [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The typical autoimmune disorders complicated with silicosis include rheumatoid arthritis (well known as Caplan syndrome) [5,6], systemic lupus erythematosus (SLE) [7,8], systemic sclerosis (SSc) [9,10], and anti-neutrophil cytoplasmic antibody (ANCA)-related vasculitis [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Complicated rheumatoid arthritis is known as Caplan's syndrome (Caplan 1959;Caplan et al 1962). Moreover, SLE (Bartsch et al 1980;Yamazaki et al 2007), systemic sclerosis (SSc) (Sluis-Cremer et al 1985;Haustein et al 1990), and anti-neutrophil cytoplasmic autoantibody (ANCA)-related vasculitis/nephritis (Saeki et al 2004;Bartůnková et al 2006) have been reported as complications of silicosis.…”
Section: Introductionmentioning
confidence: 99%
“…Inne choroby immunologiczne i nefropatie indukowane krzemionką Jak wspomniano wyżej, w wyniku niektórych badań wykazywano związek narażenia na krzemionkę z innymi chorobami immunologicznymi, takimi jak SLE [55], RZS, czy twardziną układową [42]. Poza KZN w przebiegu AAV opisano indukowany krzemionką przypadek zespołu Goodpasteura [42], a także przypadki nefropatii IgA (nephropathy IgA -NIgA) u osób narażonych na krzemionkę [56].…”
Section: Nefropatia Krzemowaunclassified